Injectable osteogenic microtissues containing mesenchymal stromal cells conformally fill and repair critical-size defects. (July 2019) - Annamalai, Ramkumar T.; Hong, Xiaowei; Schott, Nicholas G.; Tiruchinapally, Gopinath; Levi, Benjamin; Stegemann, Jan P.
Abstract: Repair of complex fractures with bone loss requires a potent, space-filling intervention to promote regeneration of bone. We present a biomaterials-based strategy combining mesenchymal stromal cells (MSC) with a chitosan-collagen matrix to form modular microtissues designed for delivery through a needle to conformally fill cavital defects. Implantation of microtissues into a calvarial defect in the mouse showed that osteogenically pre-differentiated MSC resulted in complete bridging of the cavity, while undifferentiated MSC produced mineralized tissue only in apposition to native bone. Decreasing the implant volume reduced bone regeneration, while increasing the MSC concentration also attenuated bone formation, suggesting that the cell-matrix ratio is important in achieving a robust response. Conformal filling of the defect with microtissues in a carrier gel resulted in complete healing. Taken together, these results show that modular microtissues can be used to augment the differentiated function of MSC and provide an extracellular environment that potentiates bone repair.